Exclusion and discrimination as sources of inter-ethnic inequality in Peru - Barron, Manuel (Sistema de Bibliotecas PUCP, 2008)
According to the 2003 National Household Survey, mean labour income for an indigenous worker is only 56% of that for a non-indigenous worker. Studies of ethnic discrimination in Peru’s labour markets generally find that discrimination is too low to explain inequalities of this magnitude. However, Sigma Theory (Figueroa 2003) predicts that social exclusion is a source of inter-ethnic inequality, and that has not been empirically tested. The primary aim of this paper is to fill this gap by estimating the extent to which exclusion and discrimination contribute to income inequality. Hurdle models are used to tackle down econometric endogeneity of years of schooling and truncation-at-zero of incomes. The results imply that exclusion plays a stronger role on inequality than discrimination: without exclusion, the Gini of labour income would decrease from 0.64 to 0.45, and without discrimination it would be reduced to 0.50.